2012
DOI: 10.5862/mce.30.4
|View full text |Cite
|
Sign up to set email alerts
|

Determining the bearing capacity of soil foundation reinforced by geogrid

Abstract: В основном геосинтетики используются для устройства протяженных объектов, где отношение ширины сооружения намного меньше его длины. Широкое применение армированный грунт нашел при строительстве насыпей, подпорных стен и плотин [7,8,9].Назначение геосинтетиков в грунтовых сооружениях весьма разнообразно. В плотинах их часто используют как противофильтрационные экраны [10,11]. С их помощью обеспечивают противоэрозионную защиту склонов [12], решают задачи экологической безопасности [13]. Эффективно себя зарекомен… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Based on the results of the work done, it can be concluded that the formula for the initial critical load by N.P. Puzyrevsky (2) leads to a strong overestimation of the allowable pressure, which does not correspond to the fulfillment of condition (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the results of the work done, it can be concluded that the formula for the initial critical load by N.P. Puzyrevsky (2) leads to a strong overestimation of the allowable pressure, which does not correspond to the fulfillment of condition (1).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of ground strength is of paramount importance in the practice of designing structures in determining their dimensions that satisfy the conditions of safety, durability and economy [1][2][3][4]. In modern practice, the ground strength is usually described by the Mohr-Coulomb condition according to Coulomb CA (1776), which in the formula interpretation has the following form:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geogrid is geosynthetic material widely used in embankments (Badanin and Kolosov, 2012), slopes, and retaining walls (Ibrahim, 2021). As a geotechnical structure, the grid itself and the reinforced soil are topics of research (Aleksandrov et al, 2016;Polyankin, 2020).…”
Section: Introductionmentioning
confidence: 99%